Sphagnum bleaching: Bicarbonate 'toxicity' and tolerance for seven Sphagnum species. (5th May 2022) - Koks, A. H. W.; Fritz, C.; Smolders, A. J. P.; Rehlmeyer, K.; Elzenga, J. T. M.; Krosse, S.; Lamers, L. P. M.; van Dijk, G.
Abstract: Growth and functioning of Sphagnum mosses are closely linked to water level and chemistry. Sphagnum mosses occur in wet, generally acidic conditions, and when buffered, alkaline water is known to negatively impact Sphagnum . The effects of time, dose and species‐specific responses of buffered, alkaline water on Sphagnum are largely unknown. We investigated the effects of bicarbonate and calcium on the survival, growth and physiological functioning of seven Sphagnum species occurring in contrasting environments, from raised bogs to (rich) fens. Mosses were submerged in different concentrations of bicarbonate and calcium solutions for 10 weeks under climate‐controlled circumstances. After 2 weeks, all species exposed to the high bicarbonate treatment (2.0 mM) showed severe potassium leakage and swift discoloration. In contrast, species showed differential responses to the intermediate bicarbonate treatment (0.8 mM), some with a later onset of potassium leakage. S. squarrosum, S. teres & S. contortum generally persisted the longest, with all species dying after 6 to 10 weeks. Calcium alone, in contrast, negatively affected S. squarrosum, S. teres & S. contortum, causing discoloration and potassium leakage. Our study shows enrichment with bicarbonate, but not calcium, is detrimental for most Sphagnum species tested. A mechanistic model was developed that is consistent with dose and duration dependence and the species specificity. Future conservation and restoration measures for Sphagnum ‐dominated habitats and Sphagnum farming (cultivation, production and harvest of Sphagnum moss biomass) should limit flooding with bicarbonate‐rich waters while investigating new management options, like acidifying surface waters to lower bicarbonate levels. Abstract : Bicarbonate rather than calcium proves to be toxic (dose dependent) for seven Sphagnum species from ecological contrasting environments.